Adjuvant systemic chemotherapy in the treatment of patients with invasive transitional cell carcinoma of the upper urinary tract - Kwak, Cheol; Lee, Sang Eun; Jeong, In Gab; Ku, Ja Hyeon (Urology (Ridgewood, N.J.), 2006)
To evaluate the efficacy of adjuvant systemic chemotherapy in conjunction with surgery in patients with invasive transitional cell carcinoma of the upper urinary tract. From January 1991 to May 2001, 36 men and 7 women had invasive (Stage pT2 or worse), but not metastatic, disease and were the subjects of this study. Their median age was 59 years (range 36 to 72). Of these 43 patients, 32 were scheduled to receive more than four courses of cisplatin-based chemotherapy. The median follow-up period of all the evaluated patients was 30.7 months (range 4.7 to 98.8). Recurrence was observed in 12 patients (37.5%) who underwent chemotherapy and 7 (63.6%) who did not ( P = 0.170). The disease-free survival was lower in the nonchemotherapy group than in the chemotherapy group ( P = 0.0439). During the follow-up period, 9 patients (28.1%) in the chemotherapy group died and 9 patients (81.8%) in the nonchemotherapy group died ( P = 0.004). Multivariate Cox proportional hazard model analysis revealed that the use of adjuvant chemotherapy ( P = 0.006, relative risk = 9.19) and node-positive status ( P = 0.008, relative risk = 8.28) were strongly associated with overall survival. In the chemotherapy group, 24 (75%) had side effects due to the treatment; however, fever and gastrointestinal symptoms were the chief adverse effects and were well tolerated. Our results have indicated that adjuvant systemic chemotherapy may provide therapeutic benefit in patients with invasive transitional cell carcinoma of the upper urinary tract.